Emergency Medicine Residents as Teachers: A Survey Pertaining to the Perceptions toward Teaching by Such Residents - Yasser Abdulkarem Alaska; Mohammad Hazem Alghofili; Mohammed Dhafer Al-Shehri; Hesham Hazem Alghofili; Arthur Isnani; Mohammad Saud Arafat (Wolters Kluwer Medknow Publications, 2019)
Background and Aim: There is a current trend for emergency medicine (EM) residents to adopt the role of educators within their given institution. Incidentally, such educational roles have become a part of residency training programs in many training hospitals worldwide. The current study was conducted in order to determine the perceptions of EM residents regarding their role as a teacher. Methods: A validated survey questionnaire was distributed online via Google Forms to all EM residents in six major governmental hospitals in Riyadh, Saudi Arabia. Results: A total of 76 EM residents responded to the survey. Almost 89.5% of these residents (n = 68) did not possess any previous formal training in teaching. Incidentally, 36 (47.4%) residents claimed that their institution required them to undertake a teaching role. Interestingly, a significant portion of residents (76.3%) loved to share their clinical experiences with their students. Conversely, although the majority of the residents (76.3%) felt rewarded on account of their teaching, 28.9% reported feeling stressed when they taught undergraduate medical students. Conclusion: EM residents seemed to embrace their role as teachers and deemed teaching to be a noble part of their job. It would seem, however, that, although residents gain certain benefits from teaching both academically and psychologically, there is a clear need for more in-depth formal training in teaching modalities. The amount of clinical and teaching workload should be balanced to minimize further stress among resident tutors.